Raquel González Rodríguez y Cristina Sánchez López: La negación en contraste. Madrid: Arco/Libros, 2022, 181 pp. ISBN: 978-84-7133-878-5 - Monge Hermida, Elena (Philologia Hispalensis, 2024)
Reseña del libro: La negación en contraste